Pre-Service Teachers’ Attitude toward Internet Use in Learning and Their Academic Achievement - Sulaiha; Loeneto, Bambang Apriadi; Kurniawan, Dedi (English Education:Journal of English Teaching and Research, 2021)
The internet has helped us spreading knowledge in a very swift manner and to make its accessibility available for almost everyone. It can offer the possibility to help learners, with the right attitude, to achieve better in their respective fields. This study tries to investigate the attitude of pre-service teachers in an English Education Study Program in South Sumatra toward internet use in their teaching and learning process; and to check its relationship with their academic achievement. All active students, 157 in total, in an English Education Study Program in South Sumatra, Indonesia were taken in as the subjects of the study. The data were collected using Attitude toward Internet Use in Language Learning Questionnaire and students’ cumulative GPA. The results revealed that most of the pre-service teachers showed a moderate level of positive attitude toward internet use (77.71%, 21.02% for high level, 1.27% for low level) with affective aspect as the dominant factors for the attitude (followed by behavior and cognitive aspects respectively). Furthermore, the results of the Pearson correlation indicated that there was a significant fair positive association between pre-service teachers’ attitude toward internet use in learning and academic achievement, (r(157) = .443, p = .001). This study also provided some implications and recommendations for further research.